Biological effects of Ocimum gratissimum L. are due to synergic action among multiple compounds present in essential oil - Galindo, Luciane Almeida [UNESP]; Pultrini, Aline de Moraes [UNESP]; Costa, Mirtes [UNESP] (Springer Tokyo, 2010)
Species of genus Ocimum (Lamiaceae) are economically important due to their essential oils and utilization as medicine for many disorders, including the central nervous system. A previous study showed seasonal variations in chemical profile and in central nervous system activities of essential oil from Ocimum gratissimum L. The preparation obtained in spring was able to protect the animals against tonic episodes induced by electroshock while those obtained in other seasons were effective in increasing barbiturate-induced sleeping time. The chemical analysis of essential oils showed eugenol and 1,8-cineole as principal compounds and trans-caryophyllene as a sesquiterpene in higher proportion. In the present study these three compounds were evaluated, separately or mixed in the same proportion detected in spring, in the open-field and rota-rod tests, against convulsions induced by pentylenetetrazole (PTZ; 60 mg/kg, subcutaneously, s.c.) or maximal electroshock (MES; 50 mA, 0.11 s) and in sodium pentobarbital (45 mg/kg, intraperitoneally, i.p.)-induced sleeping time. The compounds, isolated or in association, did not show efficaciousness in altering convulsive episodes, and only when in association were able to increase sleeping time duration. The absence of similar essential oil activity in the isolated compounds contributes to the idea that the major compounds are not always responsible for a biological effect observed in medicinal plant preparations. This view reinforces the concept of a multitargeted approach as a therapeutic strategy, contributing to an integrated understanding of the phenomena related to experimental activity of a complex herbal mixture.
Keywords: Synergism; Sedative; Eugenol; 1,8-Cineole; trans-Caryophyllene; Ocimum gratissimum